The current status of conservation of plant genetic resources in IBISS and related cryopreservation activities - Jevremovic, Sladana; Nikolic, Marija; Misic, Danijela; Maksimovic, Vuk; Trifunovic, Milana; Subotic, Angelina (MTT, 2008)
The presentation has two parts: to describe the current status of genetic resources stored in plant tissue culture at Institute for Biological Research Sinisa Stankovic (IBISS), Belgrade, Serbia and to present some results on fundamental aspects of cryopreservation research. The IBISS represents the largest and the most complete research institution in the field of biological sciences in Serbia. The researchers at the IBISS are primarily focused on fundamental studies in biology and are included in projects supported by Ministry of Science of Republic of Serbia. The IBISS is organized on the basis of research teams working within specific departments. The profile of researches performed at Department of Plant Physiology is characterized by basic lines of developmental plant physiology (photomorphogenesis, in vitro morphogenesis and cytodifferentiation) as well as of experimental plant biology (genetic engineering, secondary metabolite production, fungal growth and development). The IBISS has a specialized unit for experiments on in vitro plant cultures (160 m2) and developed protocols for micropropagation of more than 50 plant species. The summary of endemic, endangered and pharmaceuticaly valuable plant species kept as in vitro cultures in IBISS will be presented. Cryopreservation is a valuable alternative to the in vitro collection for conserving different types of the plant material which is planed to develop in future. Second part of presentation is some fundamental aspects of cryoprotection. This study investigated the effects of one month acclimation on the accumulation of soluble sugars (sucrose, fructose and glucose) and polyols in Fritallaria meleagris bulbs formed in culture in vitro. Analysis of carbohydrate content revealed that sucrose was the dominant soluble carbohydrate in bulblets of F. meleagris. There was no high increase of sucrose accumulation in bulblets after low temperature storage. Monosacharides (glucose and fructose) are present at significantly lower content than sucrose at standard conditions. The significantly increased accumulation of glucose and fructose in bulblets was observed after low temperature treatment but the magnitude of change was much less for glucose than for fructose. The analyses of polyol content in bulblets of F. meleagris revealed more than twice higher accumulation of sugar alcohols after low temperature treatment (Table 1). Also the SOD activity during and after acclimation will be presented.
Keywords: Ka; in vitro collection; acclimation; Fritallaria meleagris; carbohydrate content; polyol content